2016
DOI: 10.1038/aps.2016.12
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine alleviates angiotensin II-mediated renal fibrosis in mouse obstructed kidneys

Abstract: Aim: To investigate the effects of ROS scavenger N-acetylcysteine (NAC) on angiotensin II (Ang II)-mediated renal fibrosis in vivo and in vitro. Methods: Mice were subjected to unilateral ureteral obstruction (UUO), and then treated with vehicle or NAC (250 mg/kg, ip) for 7 days. Histological changes of the obstructed kidneys were observed with Masson's trichrome staining. ROS levels were detected with DHE staining. The expression of relevant proteins in the obstructed kidneys was assessed using Western blotti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 31 publications
1
29
0
2
Order By: Relevance
“…Three weeks after obstruction relief, UUO+iohexol+NAC rats had lower apoptosis rate, lower Bax mRNA expression, higher expression of Bcl-2 mRNA, and higher ratio of Bcl-2/Bax when compared with day 1 after drug administration. Only one previous study showed a role of NAC in preventing renal impairment in a model of kidney obstruction ( 18 ), but the animal model was different from the present study, which used rats instead of mice. In addition, the study by Shen et al ( 18 ) focused on the protective effect of NAC on renal fibrosis, while the present study focused on the protective role of NAC on the apoptosis of renal cells.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Three weeks after obstruction relief, UUO+iohexol+NAC rats had lower apoptosis rate, lower Bax mRNA expression, higher expression of Bcl-2 mRNA, and higher ratio of Bcl-2/Bax when compared with day 1 after drug administration. Only one previous study showed a role of NAC in preventing renal impairment in a model of kidney obstruction ( 18 ), but the animal model was different from the present study, which used rats instead of mice. In addition, the study by Shen et al ( 18 ) focused on the protective effect of NAC on renal fibrosis, while the present study focused on the protective role of NAC on the apoptosis of renal cells.…”
Section: Discussionmentioning
confidence: 56%
“…Only one previous study showed a role of NAC in preventing renal impairment in a model of kidney obstruction ( 18 ), but the animal model was different from the present study, which used rats instead of mice. In addition, the study by Shen et al ( 18 ) focused on the protective effect of NAC on renal fibrosis, while the present study focused on the protective role of NAC on the apoptosis of renal cells. Therefore, we explored different mechanisms of the protective effects of NAC.…”
Section: Discussionmentioning
confidence: 56%
“…25,33,49,51,67 Although progression of fibrosis involves several signaling pathways, the current information on the UUO model seems to suggest that preserving mitochondrial and ER function, especially the processes related to FA β-oxidation, can prevent, or at least delay, the fibrotic processes and loss of renal function. 7,23,33,51,98,120,122,123 Therefore, the steps that follow must involve not only a deeper description of the mechanisms involved in mitochondrial alterations and their pathological crosstalk with the ER, but also the temporal analysis of them. This is with the aim of developing more targeted mitochondrial therapies for future use in the clinic to treat obstructive nephropathy in patients.…”
Section: F I G U R Ementioning
confidence: 99%
“…NAC é caracterizado por ter um grupamento tiol em sua estrutura molecular e o aminoácido cisteína o torna capaz de aumentar a produção da glutationa (Bernard el at.,1984;Smillstein et al,1988). Estudos em camundongos C57BL/J6 submetidos à uninefrectomia direita e obstrução ureteral tratados ou não com NAC mostraram que a obstrução e uninefrectomia causaram a ativação do SRAA renal, aumentando a produção de H2O2, porém, o tratamento com NAC diminuiu colágeno, TGF-β, α-actina, mostrando assim uma capacidade antifibrótica e anti-inflamatória da NAC (Shen et al, 2016 anti-inflamatório e de proteção renal (Moreira et al, 2016).…”
Section: N-acetilcisteína (Nac)unclassified
“…Outra possível via da diminuição da pressão arterial seria através do SRAA já que foi observado que a infusão de NAC (5mmol/kg/hr) preveniu o aumento da pressão arterial em ratos inconscientes, e diminuiu também a ANG II plasmática o que indicaria efeitos diretos sobre a ação do SRAA por diminuir a atividade da ECA (Boesgaard et al, 2003). Já em ratos que passaram por obstrução ureteral, NAC mostrou resultados positivos ao diminuir a fibrose relacionada a ativação do SRAA via ANG II (Shen et al,2016) No presente estudo, ao analisarmos a expressão gênica de renina (Figura 40), notamos que a dieta hipersódica diminuiu esta expressão nos grupos SHAM HR e I/R HR, este resultado é esperando já que é bem estabelecido na literatura que altas concentrações de sal diminuem a ativação do SRAA (Guyton e Hall, 2006;Ferreira et al, 2010;Katayama et al, 2014), NAC como agente protetor renal fora previamente descrito em diversos estudos, promovendo aumento da proteína e gene klotho (Shimizu et al, 2012;Shimizu et al, 2016), diminuindo a fibrose intersticial, dilatação tubular e necrose tubular (Moreira et al,2016). Os achados do presente trabalho são promissores, NAC foi capaz de prevenir o desenvolvimento de albuminúria nos animais com a isquemia e reperfusão associada a uma dieta hipersódica (Figura 30), indicando que atua como protetor da barreira de filtração glomerular.…”
Section: N-acetilcisteínaunclassified